2015
DOI: 10.5588/ijtld.14.0585
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of NIH case definitions in a paediatric tuberculosis contact investigation study

Abstract: 201 wordsKey Words: Tuberculosis, paediatric, diagnosis, case definition, NIH Running head title: NIH paediatric TB research definitionSummary: We apply and compare recently proposed International Consensus (NIH) with protocol-specified case definitions for paediatric TB and describe the disease spectrum and severity in a community-based prospective cohort diagnostic TB study using household contact tracing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Although an inverse relationship between MDSC accumulation and IP‐10 production was reported previously and others demonstrated that thrombospondin‐2 is differentially expressed in a mouse model of transplant activated MDSCs, this is the first report linking plasma levels of these analytes, to peripheral MDSC frequencies in HIV and TB infections. M‐CSF is a tumour‐derived growth factor involved in monocytic differentiation, promoting in vitro expansion of MDSCs through stimulation of myelopoiesis . Counterintuitively, our results show a reduction in plasma M‐CSF in children with higher peripheral MDSC frequencies.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Although an inverse relationship between MDSC accumulation and IP‐10 production was reported previously and others demonstrated that thrombospondin‐2 is differentially expressed in a mouse model of transplant activated MDSCs, this is the first report linking plasma levels of these analytes, to peripheral MDSC frequencies in HIV and TB infections. M‐CSF is a tumour‐derived growth factor involved in monocytic differentiation, promoting in vitro expansion of MDSCs through stimulation of myelopoiesis . Counterintuitively, our results show a reduction in plasma M‐CSF in children with higher peripheral MDSC frequencies.…”
Section: Discussionsupporting
confidence: 58%
“…High levels of IDO and arginase activity has been described previously during human M.tb infection. Reports of robust IDO expression in pulmonary TB patients and lung lesions of BCG vaccinated non‐human primates , have resulted in its classification as promising prognostic marker of pulmonary TB . Similarly, increased arginase expression in TB granulomas , signify a central role for this molecule during TB disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A recent publication by Wiseman et al in which the NIH case definitions were applied to a contact investigation study, indicated that asymptomatic patients with bacterial confirmation of TB represent a continuum of disease that do warrant further evaluation. 10 CXR while useful for diagnosing intrathoracic TB, is limited by poor inter-rater agreement. 11,12 Refinement of NIH definitions to be sensitive to early disease might warrant consideration.…”
Section: Discussionmentioning
confidence: 99%
“…A useful classification system has been proposed by Wiseman et al which provides guidance on how to classify children as having severe vs. non-severe disease. 28 It may be appropriate to include only children with a confirmed diagnosis (i.e. microbiologic confirmation of the presence of Mycobacterium tuberculosis shown to be resistant by genotypic or phenotypic testing) as this gives an unambiguous entry point and allows changes in microbiological status to provide microbiological endpoints.…”
Section: Selection Of Study Population Design and Treatment Arms Fomentioning
confidence: 99%